Constitutive modeling of indentation cracking in fused silica. Issue 5 (22nd February 2017) - Bruns, Sebastian; Johanns, Kurt E.; Rehman, Hamad U.R.; Pharr, George M.; Durst, Karsten
Abstract: Fused silica shows three distinct regimes during nanoindentation, that is, plastic deformation, inelastic densification, and cracking. Cohesive zone FEM is used to study these regimes for different indenter geometries. In a three‐dimensional model, the median/radial cracking is considered by introducing cohesive element planes that are aligned along the indenter edges perpendicular to the indented surface. In addition to comparing indentation cracking data with experimental data, the role of densification on indentation crack growth is critically examined using a pressure independent von Mises and a pressure dependent Drucker‐Prager Cap constitutive model. The results show that the Drucker‐Prager Cap model delivers an accurate description of the elastic‐plastic deformation conditions for all examined indenter geometries. Material densification leads to shorter crack lengths and thus the approach by Lawn et al. ( J Am Ceram Soc, 1980;63:574‐581) results in larger indentation‐based fracture toughness values. Once the crack was initiated its propagation is comparable for blunt indenter geometries (Berkovich), while densification leads to a slower crack propagation for sharper indenter geometries.